(untitled) (Bangladesh Journal of Medical Science, 2021)
Introduction: In psychology, happiness is defined as a positive emotion which lasts longer than atemporary good feeling; it is a steady condition among one’s positive emotions and understanding oflife. Happiness is beneficial to the whole society, but the effects of happiness on university students,as the new blood and future makers of nations, have been of greater interest to researchers. Thepresent study aims to explore the factors that induce happiness in nursing and midwifery students. Methods: The present study is a descriptive-comparative work of research conducted in 2017 on 200nursing and midwifery students at the Islamic Azad University of Jahrom in the south of Iran. Thesubjects were selected based on the census sampling method. To determine the degree of happinessin the subjects, the researchers used the Oxford Happiness Questionnaire developed by Argyle et al.in 1979. The questionnaire consists of 29 multiple-choice items scored on the Likert scale between0 and 3. The reliability and validity of the questionnaire have been tested and confirmed in severalstudies. The collected data were analyzed using SPSS v. 15. Findings: Of the 200 students studied,81% (171) were female and 65.4% (138) were single. The mean happiness score of the subjects wasfound to be 40.1±9.1. On the happiness scale, the students’ happiness level was medium. 21.9% ofthe students had low happiness levels (a score of 0 to 28), 71.5% had acceptable happiness levels (ascore of 29 to 57), and 6.6% had high happiness levels (a score of 58 to 87). An analysis of the datashowed that there was not a significant relationship between the subjects’ levels of happiness and anyof their demographic characteristics except their term of study (p=0.05). Conclusion: The findingsof the present study show that the degree of happiness among nursing and midwifery universitystudents is medium. Since nursing and midwifery university students are potential labor force in thehealthcare systems of societies, it is essential that they maintain acceptable levels of happiness whichis a criterion of psychological health. Accordingly, it is recommended that organized measures betaken to improve the psychological health of students and keep it at satisfactory levels throughoutthe duration of their education. Bangladesh Journal of Medical Science Vol.20(1) 2021 p.33-38